Direct visualization of glucagon‐like peptide‐1 secretion by fluorescent fusion proteins. Issue 7 (18th April 2022) - Tsuzuki, Atsushi; Fujioka, Yoichiro; Yoshida, Aiko; Kashiwagi, Sayaka; Amano, Maho; Hira, Tohru; Nakamura, Akinobu; Miyoshi, Hideaki; Atsumi, Tatsuya; Ohba, Yusuke
Abstract: Live‐cell imaging with fluorescent proteins (FPs) is a powerful tool for investigating the exocytosis processes of hormones. However, the secretion process of glucagon‐like peptide‐1 (GLP‐1) has not been visualized by FPs, which might be because tagging FPs inhibits GLP‐1 synthesis through the post‐translational processing from proglucagon. Here, we have developed FP‐tagged GLP‐1 by inserting FPs into the middle of GLP‐1 and adding the proglucagon signal peptide. Confocal imaging confirmed that GLP‐1 fused to FPs with high folding efficiency showed granular structure, in which secretory vesicle markers colocalized. The fluorescence intensity of FP in the culture supernatant from cells treated with KCl or forskolin was significantly increased compared with those from untreated cells. Furthermore, FP‐tagged GLP‐1 enables direct visualization of stimulation‐dependent exocytosis of GLP‐1 at a single granule resolution with total internal reflection fluorescence microscopy. FP‐tagged GLP‐1 might facilitate the screening of GLP‐1 secretagogues and the discovery of new antidiabetic drugs. Abstract : We have developed fluorescent protein‐tagged glucagon‐like peptide‐1 (GLP‐1) by inserting fluorescent proteins into the middle of GLP‐1 and adding proglucagon signal peptide. Fluorescent protein‐tagged GLP‐1 enables direct visualization of stimulation‐dependent exocytosis of GLP‐1 at a single granule resolution with total internal reflection fluorescence microscopy.